Higher education’s contributions towards Malaysia’s SDG agenda: alternative futures to consider - Khalid, Haniza (2018)
Universities play a unique role in the chain of players in ESD through its ability to generate new knowledge as well as to the development of appropriate competencies and awareness in its students, future decision-makers of the world. It is expected that students coming out of ESD-driven universities can reflect, through multicultural, global and future-oriented perspectives, on their responsibility to find solutions for the local or global sustainability problems. Knowledge generated in the universities should have its origins in the problems of the people and should be translated into meaningful actions in reality. The success of any part of the Malaysia’s HE policy depends not only on the amount of planning, financial support and types of mechanism designed to deliver the desired outputs. Equally important but often neglected is the ability to navigate uncertainties and disruptive forces in today’s world that may affect the blueprint’s outcomes. As with other plans, there are an infinite number of combinations of key trends and new constraints that could force one to pause, detour, re-strategize or simply take a different path to arrive at a ‘sustainable development’ destination. This paper’s scenario analysis exercise seeks to aims to provoke and challenge HE leaders to consider alternative possibilities the future may hold, and how they might play out with respect to universities’ role to fulfill the SDG agenda.